SOCIO-ECONOMIC SITUATION IN FRANCE AFTER THE CIVIL WAR - Aslamqulova Parvina Jamshid qizi (Galaxy International Interdisciplinary Research Journal, 2023)
This article describes in detail the civil war in France and its impact on the life of the population, as well as the socio-economic life of the country after the war.